Antibiotic sensitivity reveals that wall teichoic acids mediate DNA binding during competence in Bacillus subtilis - Nicolas Mirouze (Nature Communications, 2018)
Natural genetic transformation in bacteria requires DNA binding at the surface of competent cells. Here, Mirouze et al. show that wall teichoic acids are specifically produced or modified during competence in Bacillus subtilis and promote (directly or indirectly) DNA binding at the cell surface.